Assessing the impact of factors on parental grief among older Chinese parents. Issue 2 (7th February 2021) - Zheng, Yongqiang; Wuest, Leslie G.
Abstract: A sample of 206 older Chinese bereaved parents was recruited and the effects of attachment style, coping strategy, social support, and spirituality on parental grief were investigated utilizing structural equation modeling. The results revealed problem-focused and dysfunctional coping strategy, insecure attachment style, less social support from family and friends would likely lead to higher levels of parental grief. The study explored how the unique context of Chinese culture and policies may shape the severity and duration of parental grief. It provides a baseline to understand the complexity of parental grief in China and to design and improve future interventions.